The Digital Television'́s transition in four comparative markets: Strategies and business in order to promote DTT - Urquiza García, Raquel (2022)
Nowadays Digital Terrestrial Television is a reality as well as a big opportunity for television business and the Society of Information. The policy designed is influenced by the history of each region or a country. Moreover, this topic is making a business model where the analogic television —now digital— is offered to adopt news ways of consumption, which are subordinated by technologic politics and interests of the market. The major countries, which introduced in their agendas digital television plans, are living now in the so called “transition process”. It is the moment to evaluate if the four principals markets of the European Union, the United States, Latin America, and Japan; have achieved the major goals proposed by their governments from the very beginning.